Crecimiento y desindustrialización prematura en Perú. Un análisis Kaldoriano - Jiménez, Félix (2017)
The main purpose of this study is to show if the Peruvian manufacturing industry maintains its leadership in the process of economic growth and in the increase of labor productivity, after twenty-five years of reforms and neoliberal policies. The theoretical basis of this study is Kaldorian-Keynesian, according to which economic growth is determined primarily by demand factors. Kaldor’s laws, according to which the growth of manufacturing drives growth in GDP, the growth of labor productivity in manufacturing itself and in the economy as a whole, are statistically and econometrically evaluated. The period of analysis covers 65 years from 1950 to 2015, incorporating both the period of state-led industrialization and the twenty-five years of neoliberalism also led by the State.